Dimensional stability of heat treated wood floorings - Vjekoslav Živković (University of Zagreb, Faculty of Forestry and Wood Technology, 2008)
Heat treated wood (HTW) is successfully applied for floorings due to its better moisture resistance, increased dimensional stability, and uniform colour change to darker, brownish colours. The aim of this work was to define the hygroscopic range and equilibrium moisture content at ambient conditions of heat treated wood of two wood species – ash and beech. Material was treated at two temperature levels, 190 and 210 °C, and the properties were compared with native wood. The reduction in dimensional changes is expressed by volumetric shrinking and Anti Shrink Efficiency (ASE). Additionally, parquet elements were made out of such HTW, oil-impregnated and waxed, and subsequently tested for water vapour and liquid water permeability. Shrinking gradients of HTW were not reduced in comparison with native beech wood, but the absolute reduction in water uptake resulted in cca 50 % lower EMC values and up to cca 60 % improved ASE values. Surface treatment further improved the hygroscopic properties of HTW.